(untitled) (Web of Teachers: Inderscience Research, 2024)
Sports games, especially team sports, play an important role in the personal and social development of students. They help not only to increase physical fitness, but also to develop many skills. Handball, with its dynamics and team spirit, is of particular importance in strengthening many qualities of students. In this article, we will consider in detail how to develop most qualities of students through handball games.